2013
DOI: 10.1111/jog.12227
|View full text |Cite
|
Sign up to set email alerts
|

Update on sentinel node mapping in uterine cancer: 10‐year experience at Memorial Sloan–Kettering Cancer Center

Abstract: Endometrial cancer is the most common gynecologic malignancy. In the majority of patients, the disease will present at an early stage, without metastasis, and with an excellent prognosis. Although the rate of metastasis in patients with early stage endometrial cancer is low, the standard of treatment still includes a complete or selective pelvic and para-aortic lymphadenectomy for staging. Many patients will undergo a comprehensive lymphadenectomy despite having disease confined to the uterus, resulting in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 33 publications
0
32
0
7
Order By: Relevance
“…14 We identified clinical factors, specifically lower BMI and the absence of LVSI; and surgical factors, specifically, surgeon experience in performing lymph node mapping and the use of patent blue dye, to be associated with successful mapping. Factors related to uterine pathology itself, including tumor histology, grade, method of diagnosis, the presence of an endometrial polyp, and LUSI were not found to be associated with successful mapping.…”
Section: Discussionmentioning
confidence: 99%
“…14 We identified clinical factors, specifically lower BMI and the absence of LVSI; and surgical factors, specifically, surgeon experience in performing lymph node mapping and the use of patent blue dye, to be associated with successful mapping. Factors related to uterine pathology itself, including tumor histology, grade, method of diagnosis, the presence of an endometrial polyp, and LUSI were not found to be associated with successful mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Our ability to compare staging using 18 F-FDG PET/CT with that using sentinel lymph node procedures is currently limited, as the true performance in endometrial carcinomas is not well established because the studies have been small and the techniques applied have often varied (26). A recent update from the Memorial Sloan Kettering Cancer Center after 10 y of experience with sentinel lymph node mapping in uterine cancer concluded that prospective studies are needed to validate the use of sentinel lymph node mapping in early-stage endometrial cancer (27). Interestingly, the negative predictive value in the present study was very high (97%-98%), confirming the 95% reported by Criverallo et al (13) and the 96% reported by Antonsen et al (22).…”
Section: Discussionmentioning
confidence: 99%
“…23 The analysis of histotype, miometrial invasion, and grading remains the only way to predict the risk of lymph nodal metastasis.…”
Section: In 2009mentioning
confidence: 99%